A Modern Strategy for the Development of Academic Staff Based on University-Industry Knowledge Transfer Effectiveness & Collaborative Research - Saima, Iqbal; Abeda, Muhammad Iqbal; Adnan, Shahid Khan; Aslan, Amat Senin (UTM Press, 2013)
University and industry has substantially contributed to enhancing the quality of life. As a result, trans-disciplinary scientific communities have come to play a vital role to produce new knowledge with effective applications for rapid technological change and innovation to be a competitive globally. For this purpose study provide a framework for the development of academic staff of higher education. We used University-Industry collaboration as the channel to develop and encourage teachers, doctors, professors and researchers with the help of research relationship. The paper contributes to the literature on university-industry interactions to improve applied knowledge, skills and practices of academic staff and enhancement on technology innovation and commercialization. Secondly, our aim to provide an efficient mechanism of knowledge transfer effectiveness (KTE) and collaborative research (CR) those are available to transfer and share knowledge and information from university to industry effectively and to eliminate major obstacles of knowledge transfer by using productive knowledge transfer indicators (KTIs). Research findings indicates the question is, how the process of university-industry interaction will be managed at different stages for the success of knowledge transfer and how knowledge gap is reduced through effective interactions. By adopting this framework any university or industry can easily cross the threshold in the grown-up academic and research collaborational community.